Treatment persistence in patients with rheumatoid arthritis and ankylosing spondylitis - Marina Amaral de Ávila Machado; Cristiano Soares de Moura; Felipe Ferré; Sasha Bernatsky; Elham Rahme; Francisco de Assis Acurcio (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To evaluate treatment persistence in patients with rheumatoid arthritis and ankylosing spondylitis who started therapies with disease-modifying antirheumatic drugs (DMARD) and tumor necrosis factor blockers (anti-TNF drugs). METHODS This retrospective cohort study from July 2008 to September 2013 evaluated therapy persistence, which is defined as the period between the start of treatment until it is discontinued, allowing for an interval of up to 30 days between the prescription end and the start of the next prescription. Odds ratio (OR) with 95% confidence intervals (95%CI) were calculated by logistic regression models to estimate the patients' chances of persisting in their therapies after the first and after the two first years of follow-up. RESULTS The study included 11,642 patients with rheumatoid arthritis - 2,241 of these started on anti-TNF drugs (+/-DMARD) and 9,401 patients started on DMARD - and 1,251 patients with ankylosing spondylitis - 976 of them were started on anti-TNF drugs (+/-DMARD) and 275 were started on DMARD. In the first year of follow-up, 63.5% of the patients persisted in their therapies with anti-TNF drugs (+/-DMARD) and 54.1% remained using DMARD in the group with rheumatoid arthritis. In regards to ankylosing spondylitis, 79.0% of the subjects in anti-TNF (+/-DMARD) group and 41.1% of the subjects in the DMARD group persisted with their treatments. The OR (95%CI) for therapy persistence was 1.50 (1.34-1.67) for the anti-TNF (+/-DMARD) group as compared with the DMARD group in the first year for the patients with rheumatoid arthritis, and 2.33 (1.74-3.11) for the patients with ankylosing spondylitis. A similar trend was observed at the end of the second year. CONCLUSIONS A general trend of higher rates of therapy persistence with anti-TNF drugs (+/-DMARD) was observed as compared to DMARD in the study period. We observed higher persistence rates for anti-TNF drugs (+/-DMARD) in patients with ankylosing spondylitis as compared to rheumatoid arthritis; and a higher persistence for DMARD in patients with rheumatoid arthritis as compared to ankylosing spondylitis.